Improving Basic Pencak Silat Movement Skills Through a Motor Learning Approach for Beginners at High School Level - Harvi, Novhal Pramudia; Yuanda, Dea Mona; Ritonga, Ahmad Syarif; Habibi, MHD Ray; Dewi, Rahma; Barus, Jan Bobby Nesra (Holistic Science, 2025)
This study aims to develop a learning model for basic pencak silat techniques specifically designed for children aged 10–12 years. This model is based on a motor learning approach that includes three stages: the cognitive stage (understanding movements), the associative stage (practice with correction), and the automation stage (fluent movements without thinking). This study uses the Classroom Action Research (CAR) method which is implemented through four stages: planning, implementation, observation, and reflection. The subjects of the study were 10 students from a pencak silat training center in City Medan. The training process was carried out for four weeks with a schedule of two to three times per week, covering material on horse stances, stances, punches, blocks, and movement combinations. Data were collected through technique observation sheets, physical tests (including balance, strength, coordination, and flexibility), and motivation questionnaires. The results of the study showed a significant increase in students' mastery of techniques and motor skills. The average motor test score increased from 60 to 78. In addition, students became more confident, active, and enthusiastic in participating in training. In conclusion, this gradual learning model is effectively applied in basic level pencak silat training and can be a reference for PJOK teachers and beginner pencak silat trainers.